Training of Visual Comic Media with Agricultural Theme for Nurul Islam Learning Community Teachers, Tengaran, Jawa Tengah - Kusmaryono, Imam; Abdul Basir, Mochamad; Dhani, Ali Umar (Indonesian Journal of Community Services, 2025)
SMP IT Nurul Islam Tengaran, as part of the Nurul Islam Learning Community, faces the problem of low student motivation and engagement in numeracy learning due to the use of traditional learning media. To address this challenge, this community service program was implemented with the aim of improving teacher capacity through training in the creation of audio-visual comics themed on local agricultural wisdom. The activity was attended by 30 teachers and was carried out through several stages, namely needs analysis, comic design training, production assistance, learning trials, and evaluation. The results of the implementation showed a significant increase in teachers' ability to produce digital teaching materials, with an average score increasing from 42.5% to 88.7%. The implementation of agricultural-themed audio-visual comics in learning showed a 35% increase in student participation in class discussions and an 82% increase in numeracy literacy skills. These results confirm that local wisdom-based audio-visual comics are effective in strengthening numeracy literacy while improving the quality of learning in schools.